Les pays socialistes de l’Est et l’Unité Européenne - La tradition dans le socialisme et le socialisme dans la tradition : iI. De l’hostilité à la coopération avec la Communauté européenne - Pilisi, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
From its beginnings in 1922, the foreign policy of the Soviet Union has pursued one overriding objective : the preservation of the empire. This policy's dialectic is in conformity with the Soviet doctrine which holds that international relations are but relations of production. Soviet foreign policy has always sought international legal guarantees to protect the conquests of empire and socialism. Ideologically, the U.S.S.R. has always been opposed to the idea of European unity. European integration has traditionally been viewed by the Soviet empire as the ultimate endeavour of capitalism prior to the latter's final crisis. This basic policy option had been adopted by the socialist countries of Europe.From 1922, when the Soviet Union had accorded the E.E.C. de facto recognition, several countries of Eastern Europe had expressed their respective attitudes with regard to European integration. The Helsinki and Belgrade C.S.C.E., the final result of which was only a diplomatic declaration, emphasized the idea of East-West cooperation. European cooperation, deriving from a compromise between economic "necessity" and political "illusion," should provide practical results rather than ideas. De jure recognition of the E.E.C. by the U.S.S.R. and the Eastern Europe countries also constitutes an important element of East-West relations. The 1980s will reveal whether or not the hostility of the countries of Eastern Europe with respect to European integration has definitely been replaced by cooperation free from ulterior ideological motives.